2017
DOI: 10.1140/epjc/s10052-017-4977-4
|View full text |Cite
|
Sign up to set email alerts
|

Duality between k-essence and Rastall gravity

Abstract: The k-essence theory with a power-law function of (∂φ) 2 and Rastall's non-conservative theory of gravity with a scalar field are shown to have the same solutions for the metric under the assumption that both the metric and the scalar fields depend on a single coordinate. This equivalence (called k-R duality) holds for static configurations with various symmetries (spherical, plane, cylindrical, etc.) and all homogeneous cosmologies. In the presence of matter, Rastall's theory requires additional assumptions o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 24 publications
2
58
0
2
Order By: Relevance
“…Also, it is apparent that for a traceless energy-momentum source, such as the electromagnetic source, we have S µν = T µν which leads to G µν = κT µν . This means that the Einstein solutions for T = 0, or equivalently R = 0, are also valid in the Rastall theory of κ [13,20]. Moreover, it should be mentioned that both of the parameter cases γ = are not allowed as discussed in [17].…”
Section: Rastall Theory Of Gravitymentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it is apparent that for a traceless energy-momentum source, such as the electromagnetic source, we have S µν = T µν which leads to G µν = κT µν . This means that the Einstein solutions for T = 0, or equivalently R = 0, are also valid in the Rastall theory of κ [13,20]. Moreover, it should be mentioned that both of the parameter cases γ = are not allowed as discussed in [17].…”
Section: Rastall Theory Of Gravitymentioning
confidence: 99%
“…For example, by special setting of the parameters of the Rastall theory, a vacuum solution possessing the same structure as the Schwarzschildde Sitter solution in the general relativity theory obtained with a cosmological constant playing the role of source [19]. In another work, the problem of finding static spherically symmetric spaces in Rastall's theory in the presence of a free or self interacting scalar field is studied [20]. It is found that some exact solutions can be obtained in which some of these solutions are the same as the solutions which are obtained in the context of k-essence theory.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we consider an Ellis wormhole in General Relativity [1][2][3][4][5][6][7][8]. Such a wormhole connects two asymptotically flat spacetimes by a throat.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we can combine equation (46) and equation (47) and define Here, the next step is to analyze the sign of Eq. (48).…”
Section: Weak Cosmic Censorship Conjecture With Pressure and Volumementioning
confidence: 99%